Thermal Control for Metal Condition Testing in Pipelines of Nucltar Power Plant - Meshkov, S. M.; Orel, R. P. (My University, 2017)
The thermographic examination results of nuclear power plant high pressure pipelines and main condensate pipelines are considered. The conditions and technique of several sections thermal control are specified. It is found, that cavitation defects have a "heat trace". The use of thermography as an effective express-control method for quick determining the temperature anomalies space for a detailed study of other methods is proposed
Keywords: thermography; hidden defects; external factors; cavitation; high pressure steam lines; main condensate